A Combined Treatment with Berberine and Andrographis Exhibits Enhanced Anti-Cancer Activity through Suppression of DNA Replication in Colorectal Cancer - Yinghui Zhao; Souvick Roy; Chuanxin Wang; Ajay Goel (MDPI AG, 2022)
The high morbidity and mortality associated with colorectal cancer (CRC) are largely due to the invariable development of chemoresistance to classic chemotherapies, as well as intolerance to their significant toxicity. Many pharmaceutical formulations screened from natural plant extracts offer safe, inexpensive, and multi-target therapeutic options. In this study, we demonstrated that Berberis vulgaris L. (Berberine) and Andrographis paniculata (Burm. f.) Nees (Andrographis) extracts exerted their synergistic amplified anti-cancer effects by jointly inhibiting cell viability, suppressing colony formation, and inducing cell cycle arrest. Consistent with our in-vitro findings, the amplified synergistic anti-cancer effects were also observed in subcutaneous xenograft preclinical animal models, as well as patient-derived primary tumor organoids. To explore the molecular mechanisms underlying the amplified synergistic anti-cancer effects, RNA sequencing was performed to identify candidate pathways and genes. A transcriptome analysis revealed that DNA-replication-related genes, including FEN1, MCM7, PRIM1, MCM5, POLA1, MCM4, and PCNA, may be responsible for the enhanced anticancer effects of these two natural extracts. Taken together, our data revealed the powerful enhanced synergistic anti-CRC effects of berberine and Andrographis and provide evidence for the combinational targeting of DNA-replication-related genes as a promising new strategy for the therapeutic option in the management of CRC patients.